Unsteady Aerodynamics - Potential and Vortex Methods - Dimitriadis, Grigorios; Belobaba, Peter; Cooper, Jonathan; Seabridge, Allan (John Wiley & Sons, 2024)
A comprehensive overview of unsteady aerodynamics and its applicationsThe study of unsteady aerodynamics goes back a century and has only become more significant as aircraft become increasingly sophisticated, fly faster, and their structures are lighter and more flexible. Progress in the understanding of flow physics, computing power and techniques, and modelling technologies has led to corresponding progress in unsteady aerodynamics, with a wide range of methods currently used to predict the performance of engineering structures under unsteady conditions.This book offers a comprehensive and systematic overview of the application of potential and vortex methods to the subject. Beginning with an introduction to the fundamentals of unsteady flow, it then discusses the modelling of attached and separated, incompressible and compressible flows around two-dimensional and three-dimensional bodies. The result is an essential resource for design and simulation in aerospace engineering.The book readers will also find:MATLAB examples and exercises throughout, with codes and solutions on an accompanying websiteDetailed discussion of most classes of unsteady phenomena, including flapping flight, transonic flow, dynamic stall, flow around bluff bodies and moreValidation of theoretical and numerical predictions using comparisons to experimental data from the literature